Microemulsion Assisted Assembly of 3D Porous S/Graphene@g‐C3N4 Hybrid Sponge as Free‐Standing Cathodes for High Energy Density Li–S Batteries - Zhang, Juan; Li, Jin‐Yi; Wang, Wen‐Peng; Zhang, Xing‐Hao; Tan, Xing‐Hua; Chu, Wei‐Guo; Guo, Yu‐Guo (Advanced energy materials, 2018)
A 3D porous sulfur/graphene@g‐C3N4 (S/GCN) hybrid sponge, which can be directly applied as a free‐standing cathode for Li–S batteries, is realized via a microemulsion assisted assembly approach. In this strategy, the interior oil emulsion droplets serve as soft templates to form pores to accommodate sulfur and the hydrophilic GCN stacks around oil droplets to assemble into a crosslinked 3D network. Through this microemulsion encapsulation route, S/GCN cathodes with a sulfur loading as high as 82 wt% can be achieved. Furthermore, the enriched N‐sites in GCN macropores offer numerous adhesion sites for polysulfides, realizing a “physical‐chemical” dual‐confinement for polysulfides from diffusion. Moreover, the robust and highly porous 3D graphene frameworks render efficient electron/Li+ transport pathways for fast kinetics as well as good structure integrity. Consequently, in comparison to the conventional G‐sponge/Li2Sn catholyte system, S/GCN delivers a higher specific capacity, superior high‐rate capability (612 mA h g−1 at 10 C), and alleviated anode corrosion issues. Particularly, an energy density as high as 1493 W h kg−1 (calculated on the total weight of the cathode) and an extremely low capacity fading rate of 0.017% per cycle over 800 cycles at 0.3 C are achieved. Oil‐in‐water microemulsion assembly of 3D porous S/graphene@C3N4 (S/GCN) sponge is proposed as a free‐standing cathode for Li–S batteries. The oil emulsions serve as templates for macropores to accommodate sulfur, while the GCN stacks around oil droplets to assemble into interlinked 3D network. The S/GCN exhibits superior high‐rate capability (612 mA h g−1 at 10 C) and stable long‐term cycling over 800 cycles.